Tin man - Madson, Justin (New York : Amulet Books, 2022)
"In Justin Madson's debut graphic novel, Tin Man, a girl and her brother befriend the titular Tin Man with unexpected results. Solar is in her last year of high school and is reeling from the recent death of her grandmother. She has abandoned her plans for the future and fallen in with a bad crowd. Her little brother Fenn doesn't understand why she's changed-she doesn't even want to help him build their rocket in the garage anymore. Campbell is a tin woodsman- a clunky, metal man whose sole purpose in life is to chop down trees. He longs for more, however, and decides to seek out a heart, believing that, with one, he will be able to feel things he has never felt before and, therefore, change his life. Equal parts The Iron Giant, The Wizard of Oz, Edward Scissorhands, and Freaks and Geeks, Tin Man is a story about finding friendship in the unlikeliest of places"--Provided by publisher.
Junior Library Guild
Ages 14 & Up.
Grades 9 & Up.
A Junior Library Guild selection (JLG)
Keywords: Friendship -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Inventions -- Juvenile fiction; Engineering -- Juvenile fiction; Grief -- Juvenile fiction; Oz (Imaginary place) -- Juvenile fiction